The Role of the Kyai in Shaping Community Preferences: Mediating the Impact of Service Quality and Teacher Commitment - Hasan Baharun; Sabran Sabran; Mukhamad Ilyasin; M. Abzar Duraesa; Putri Fahmadia Dinda Maulida Thohir; Abdul Wahid Zaini (Jurnal Pendidikan Islam, 2025)
Islamic boarding schools in Indonesia are growing rapidly, yet many still struggle to maintain competitiveness and community trust. This study examines the influence of service quality and work commitment on preferences in choosing pesantren, with patronage figures (kyai) as mediating variables. Using a quantitative explanatory causal design, data were collected from 380 respondents, consisting of students and guardians at Nurul Jadid Islamic Boarding School, East Java. The data were analyzed with Partial Least Squares–Structural Equation Modeling. The results reveal that service quality significantly affects both patronage figures (β = 0.502, p < 0.001) and preferences (β = 0.243, p < 0.01), whereas work commitment significantly influences patronage figures (β = 0.354, p < 0.001) but has no direct effect on preferences (β = 0.096, p = 0.212). Patronage figures have the strongest impact on preferences (β = 0.539, p < 0.001) and mediate the effects of both service quality (β = 0.475, p < 0.001) and work commitment (β = 0.233, p < 0.001). These findings confirm that technical factors such as service quality and teacher commitment shape community preferences only when reinforced by the authority and legitimacy of kyai leadership. The study advances the SERVQUAL and Social Exchange frameworks in faith-based education and suggests that pesantren should integrate service improvements with stronger leadership visibility to sustain community loyalty and institutional competitiveness. The research implies that to effectively increase community preference for Islamic boarding school institutions (pesantren), institutions must not only focus on tangible improvements in service quality but also strategically emphasize the selection and visibility of a respected patronage figure (kyai) who possesses strong legitimacy in the eyes of the community.